Immunogenicity and safety among laboratory workers vaccinated with Bexsero® vaccine - Eva Hong; Aude Terrade; Muhamed-Kheir Taha (Human Vaccines & Immunotherapeutics, 2017)
Neisseria meningitidis serogroup B is the most prevalent cause of invasive meningococcal disease in Europe and members of laboratories working on meningococci are at risk due to frequent handling. Recommendation for anti-meningococcal vaccination among these workers has been recently updated upon the licensure in Europe of Bexsero® vaccine. We tested the immunogenicity and safety of this vaccine among adults laboratory staff using the recommended schedule of 2 doses at 5 weeks interval. The vaccine was well tolerated in spite of frequent local side effects and all participants reported at least one side effect after each dose. Immunogenicity was evaluated 6 weeks and one year after the second dose. All participants showed increase in their bactericidal titers against the components of the vaccine 6 weeks after the second dose, however titers declined significantly one year later.